Circulating microRNAs as biomarker in prostate cancer and their significance in the differentiation of benign and malignant conditions of the prostate - Kowsalya Ramprasad; Madhura Navule Siddappa; Manohar Chikkamoga Siddaiah; Manju Moorthy; Gopalakrishna Ramaswamy (Urology Annals)
Background: Prostate cancer is among the most commonly diagnosed cancers in males worldwide. While Prostate-specific antigen (PSA) remains the front-line screening marker, it lacks sufficient diagnostic accuracy. Aims and Objectives: So, in the quest for improved biomarkers, the expression profiles of circulating miRNAs have become increasingly significant. Hence, this study was undertaken to identify the miRNA profile unique to prostate cancer. Materials and Methods: Using NanoString Human MicroRNA Arrays, we analyzed serum samples from three groups: patients with localized prostate cancer, metastatic prostate cancer, and benign prostatic hyperplasia. Results: Our analysis revealed distinct circulating miRNA expression patterns in prostate cancer patients compared to those with benign conditions. Specifically, miR-1272 and miR-1247-5p were significantly up-regulated (log2FC > 1, p < 0.05), whereas miR-337-3p, miR-191-5p, and let-7a-5p were significantly down-regulated (log2FC < -1, p < 0.05) in prostate cancer versus BPH. Additionally, when comparing localized and metastatic prostate cancer, hsa-miR-302d-3p and hsa-miR-1246 were notably up-regulated (log2FC > 3, P < 0.05). These specific miRNAs show potential for facilitating early diagnosis, enhancing risk stratification, and serving as non-invasive biomarkers for monitoring disease progression, thereby helping to reduce the need for unnecessary biopsies. Conclusions: Our findings suggest that circulating miRNAs could serve as minimally invasive biomarkers in prostatic cancer with a higher specificity and sensitivity, making them more effective at distinguishing between cancerous and benign conditions. However, despite their promise, miRNA testing remains costly, technically complex, and not yet standardized for routine clinical use. Therefore, further validation in larger, independent cohorts is essential to confirm the diagnostic and prognostic utility of the miRNAs identified in this study.